2014
DOI: 10.1680/geot.13.p.056
|View full text |Cite
|
Sign up to set email alerts
|

Environmental degradation of claystones

Abstract: The paper presents the results of a comprehensive experimental programme carried out to study the effects of relative humidity cycling on the degradation of argillaceous rocks. Lilla claystone, a lowporosity Tertiary rock, was used for this purpose. Four aspects were analysed: (a) the influence of the number of relative humidity cycles; (b) the amplitude of relative humidity cycles; (c) the stress level; and (d) the effects of using liquid water or vapour during wetting paths. The application of relative humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…The applied RH cycles caused an irreversible increase in the specimens' volumes as swelling always exceeded the amount of shrinkage. Pineda et al (2014) found that higher peak-to-peak amplitudes in RH cycles (cycles between 20 and 99 % were compared to cycles between 50 and 99 %) led to larger volumetric swelling. This effect was less pronounced for specimens that were tested under higher confinements.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The applied RH cycles caused an irreversible increase in the specimens' volumes as swelling always exceeded the amount of shrinkage. Pineda et al (2014) found that higher peak-to-peak amplitudes in RH cycles (cycles between 20 and 99 % were compared to cycles between 50 and 99 %) led to larger volumetric swelling. This effect was less pronounced for specimens that were tested under higher confinements.…”
Section: Introductionmentioning
confidence: 93%
“…Few studies exist in which the influence of cycles in RH on the drying-swelling characteristics of clay shales has been investigated (e.g. Grice, 1968;Van Eeckhout, 1976;Olivier, 1979;Pham et al, 2007;Farulla et al, 2010;Cardoso et al, 2011;Yang et al, 2012;Pineda et al, 2014). Grice (1968) noted that specimens of Utica shale that were immersed in water disintegrated completely after oven drying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preceding discussion indicates that two main effects control weathering: the atmospheric cycles (evaporation-rainfall induced wetting) and the confinement stress. An investigation of the damage induced by cycles of suction change at different isotropic confining pressures was reported by Pineda et al (2013). Core samples of Lilla claystone, a similar low plasticity dense claystone to Castrovido, were subjected to stress-suction cycles paths involving different confining stresses and a varying intensity of suction change (Pineda et al, 2013).…”
Section: Weatheringmentioning
confidence: 99%
“…An investigation of the damage induced by cycles of suction change at different isotropic confining pressures was reported by Pineda et al (2013). Core samples of Lilla claystone, a similar low plasticity dense claystone to Castrovido, were subjected to stress-suction cycles paths involving different confining stresses and a varying intensity of suction change (Pineda et al, 2013). Sample stiffness was measured during testing by P and S-wave transmission.…”
Section: Weatheringmentioning
confidence: 99%